Bioethanol Production from Olive Solid Residues by Using Rhodotorula Minuta - Al-Rubaie, Sundus Khudair; Abdulhay, Hind Suhail (Iraqi Journal of Science, 2022)
Bioethanol is an attractive fuel with higher potential for energy security and environmental safety. Olive solid residues were used as a raw material for the production of bioethanol through the use of different preliminary treatments . Separate treatments with cellulose, hydrochloric acid (HCl 5%), sulfuric acid (H2SO4 2%), and liquid ammonia NH4OH (20%) were used to convert cellulose and hemicellulose into monosaccharaides. The production of ethanol was observed during the fermentation process using R. minuta under anaerobic conditions. After 3 days of fermentation, lowest concentrations of ethanol of 0.233, 0.249, 0.261, and 0.275 g/ l were produced from olive waste powder sample as a result of separate pretreatment with cellulase, hydrochloric acid (HCl 5%), sulfuric acid (H2SO4 2%), and liquid ammonia NH4OH (20%), respectively, whereas the untreated sample showed ethanol yield of 0.264 g/ l.. The highest ethanol concentrations for the same samples were 0.510, 0.564, 0.737, and 0.696 g/ l, respectively, whereas that for the untreated samples was 0.445 g/ l. The highest concentration of ethanol produced (0.737 g/ l) was achieved after 3 days of fermentation of olive solid waste pretreated with H2SO4 2% at 30 oC and pH 5. The average yield of ethanol resulted from these saccharification and fermentation processes following the pretreatment of olive solid waste was 0.59 g/10 g dry olive solid residues.